Disaster risk reduction of Mount Kelud eruption based on capacity building: A case study in Kasembon District, Malang Regency - Rahmawati, Dwi; Rachmawati, Turniningtyas Ayu; Prayitno, Gunawan (Centre for Science and Technology, IAIN Surakarta, 2018)
The ability to respond and recover from disasters is highly dependent on the community’s capacity. This study assessed the community’s capacity level in Kasembon District, an area that was impacted by the Mount Kelud eruption in 2014. Capacity level assessment is done by identifying pentagon asset components, covering human capital, social capital, financial capital, natural capital and physical capital. Bayem is a village with the medium capacity in spite of the low ownership of natural capital, financial capital and physical capital as it has been supported by the active participation of the community within the village organization. Pondok Agung, Kasembon, Sukosari and Pait are four villages which are almost the same with Bayem, but the involvement of the community is not as active as in Bayem. Based on the results of the research, villages that are socially active, tend to have a higher capacity.